Diversity of salmonella typhi-phages in Dhaka city through whole genome sequencing - Islam, Shuborno (Brac University, 2024)
This thesis submitted to the Department of Mathematics and Natural Sciences in partial fulfillment of the requirements for the degree of Master of Science in Biotechnology, 2024.